EFFECT OF PLANTATION ESTABLISHMENT AND RAW MATERIAL STABILIZATION ON THE USEFULL TRAITS OF LOVAGE LEAVES (Levisticum officinale Koch.) - Wiesława Rosłon; Ewa Osińska; Anna Wajs-Bonikowska (Acta Scientiarum Polonorum: Hortorum Cultus, 2013)
Lovage is a popular medicinal and spice plant. Its usable organs are roots, fruits and leaves. The aim of this study was to evaluate the influence of plantation establishment and different methods of lovage leaves stabilization on its functional characteristics, including the essential oil content, chemical composition and quality of odor. Higher content of essential oil was determined in leaves harvested from plantations established with seedlings in comparison to the one from late fall sowing (respectively: 0.890 ml.100 g-1, 0.755 ml.100 g-1). Freezing, oven-drying and freeze-drying resulted in a decrease of this substance content. Compounds present in the tested essential oils were monoterpenes and their oxygen-containing derivatives (an average of 80.2%). The main component in the analysed essential oils was the -terpinyl acetate (average 36.6%). Percentage of -terpinyl acetate, (Z)-ligustylid, (Z)-butylidenoftalid, (E)-butylidenoftalid and (E)-ligustylid increased under the used stability methods. Appearance in the oils collected from stabilized raw materials trans-p-menth-2-en-1-ol, cis-β-elemene, and butylophtalide (compounds that were absent in the essential oil from fresh raw material) was also observed.